Role of atmospheric wave interaction in the generation Of easterly zonal current in the monsoon region - SINGH, M. P.; SARMA, G. N.; DATTA, R. K.; Raghava, R. C. (MAUSAM, 1984)
One of the significant semi-permanent features of the monsoon circulation of the tropical easterly jet (TEJ). The present paper is an attempt to study the contribution from interaction amongst various waves tropical regions towards the generation of the TEJ. The multiple scale technique has been used to energy exchange process amongst the significant flow patterns of the monsoon circulation. Specifically, we have considered eleven sets of wave triads under the condition of resonance and it is noted that three of these support excitation or generation of TEJ type structure.